Acidity Level of Chicken Egg Consumption by Soaking Coffee Leaves - Irpan; Abdul Hakim Fattag; Mangalisu, Azmi (International Journal of Animal Science, 2024)
This research aims to determine the acidity level of chicken eggs consumed by soaking coffee leaves. This research method used a Completely Randomized Design (CRD) consisting of 4 treatments with 3 replications, namely R0: Without soaking coffee leaves (control), P1: 10% soaking coffee leaves, P2: 20% soaking coffee leaves and P3: 30% soaking coffee leaves. The variables measured are pH (degree of acidity), water content, total titration acid. The results of this study showed that the treatment had no significant effect on the average water content. The level of preference for consumption of eggs is found in the 0% treatment. The results of this research on yolk pH (egg yolk pH), namely 0% coffee leaf immersion, amounted to 6.47, 10% coffee leaf immersion, amounted to 7.63, 20% coffee leaf immersion, amounted to 8.20, 30% coffee leaf immersion , amounting to 9.53. pH of albumen (pH of egg white) soaking coffee leaves 0%, amounting to 6.73, soaking coffee leaves 10%, amounting to 7.87, soaking coffee leaves 20%, amounting to 8.40, soaking coffee leaves 30 %, amounting to 9.57. The water content with 0% coffee leaf immersion is 91.00, 10% coffee leaf immersion is 93.33, 20% coffee leaf immersion is 91.66, 30% coffee leaf immersion is 92.66. on the total titration principle of 0% coffee leaf immersion, amounting to 6.90, 10% coffee leaf immersion, amounting to 2.40, 20% coffee leaf immersion, amounting to 5.40, 30% coffee leaf immersion, amounting to 11.10. The conclusion of this research is that consumption eggs soaked in coffee leaves have a significant effect on yolk pH, albumen pH and total titratable acid but have no significant effect on water content